Neoantigen vaccine-induced CD4 T cells confer protective immunity in a mouse model of multiple myeloma through activation of CD8 T cells against non-vaccine, tumor-associated antigens. Issue 2 (21st February 2022) - Bekri, Selma; Rodney-Sandy, Reunet; Gruenstein, Diana; Mei, Anna; Bogen, Bjarne; Castle, John; Levey, Daniel; Cho, Hearn Jay
Abstract : Background: Cancer-associated neoantigens (neoAg) derived from tumor genomic sequencing and predictive algorithms for mutated peptides are a promising basis for therapeutic vaccines under investigation. Although these are generally designed to bind major histocompatibility complex class I and induce CD8 cytolytic T lymphocyte (CTL) activity, results from preclinical and clinical studies demonstrate that the majority of neoAg vaccines efficiently induce CD4 T helper (Th) responses but not CTL. Despite this, these vaccines have demonstrated clinical efficacy. Therefore, understanding the mechanisms of CD4 + T cell-mediated tumor protection is critical to optimizing this immunotherapeutic strategy. Methods: We investigated this phenomenon in the mineral oil-induced plasmacytoma (MOPC).315.BM (MOPC315) mouse model of multiple myeloma, a malignancy of plasma cells. MOPC315 cells express in their lambda chain a unique tumor-specific neoAg, an idiotypic (Id) peptide. We generated a vaccine formulated with this Id peptide fused to a heat shock protein HSC70 binding (HSB) motif co-delivered with poly (I:C). The immunogenicity of the Id-vaccine was measured in splenocytes by ELISpot. Mice were challenged with MOPC315 cells and antitumor immunity was assessed by co-incubating splenocytes and bone marrow mononuclear cells derived from vaccinated mice and controls, with the Id antigen and irradiated MOPC315 cells. The frequency of activated CD4 and CD8 T cells and their phenotype were characterized by flow cytometry. Results: Id-vaccine efficiently induced antigen-specific CD4 Th activity and antitumor immunity, protecting mice from MOPC315 tumor growth. CD4 cytolytic activity was not detected under these conditions. Polyfunctional CD8 T cells homed to the bone marrow microenvironment of protected mice and preferentially expanded only when restimulated ex vivo with both Id peptide and MOPC315 cells. Protective activity was abrogated by depletion of either CD4 or CD8 lymphocytes. Conclusion: These results demonstrate that Id-HSB +poly (I:C) vaccine protects against MOPC315 growth by priming Id-specific CD4 Th cells that confer protection against tumor but are not directly cytotoxic. These data indicate that activation of CD8 CTL against MOPC315-associated antigens not present in the vaccine is one of the major mechanisms of tumor immunity.